(untitled) (Studia Prawnicze / The Legal Studies, 2023)
In the article it has been indicated that the traditional model of lease does not correspond with the present socio-economic situation. Therefore substantive transformations are required to distinguish between two independent legal institutions: the lease of movable and immovable property, and the lease of the agricultural one. The latter should be distinguished de lege ferenda. The conditions of the latter lease should be made uniform, irrespective of the nature of ownership of the leased property. Moreover a further division should be made into a long and short — term lease. The author has attempted at a future, modern model of agricultural lease, treated as a legal relationship regulated by both civil and administrative law. She has pointed out the aspects of the said relationship which ensure that the land is rationally utilized, particularly the rights and duties of a tenant farmer as an agricultural producer, other factors that account for effective exploitation of the leased land (i.e. the agricultural qualifications of the tenant, a rent, the amount of the leased land) and legal measures that ensure productive efficacity of the agricultural lease (preferences in the purchase of feeds, fertilizers, state assistance pertaining to credits, benefits, exemption from taxes, legal protection of the tenant, etc.).